Between social documentary and a global aesthetic: the use of landscape by early-career South African photographers. (4th May 2022) - Kirkwood, Meghan L. E.
Abstract : This article examines work from three South African artists—Vincent Bezuidenhout, Renzske Scholtz, and Jabulani Dhlamini—and argues that they use landscape images to find alignment or clarity between themselves, the social and political history of their country, and its land. Caught between a generation of activists who immersed themselves in views of a contested landscape, and another generation who did not experience life under apartheid, these photographers must balance what they see in the landscape in a contemporary context and its history into their representations. In "Separate Amenities, " Bezuidenhout examines how segregated recreational areas inscribed racist views into the South African coastline. In her series "The Farm, " Scholtz uses triptychs to combine archival imagery, contemporary photographs, and personal artifacts from a family property that was bought by the apartheid state and used as a prisoner camp. Jabulani Dhlamini revisits locations in the Sharpeville township connected to the 1960 Sharpeville Massacre. Finally, this article asserts that the landscape medium offers artists such as Bezuidenhout, Scholtz, and Dhlamini a space in which to mediate and engage the influence of the social documentary tradition in a post-apartheid art-making context—all while developing their identities as professional artists engaged in a global photographic dialog.